The Influence of Emotional Value, Social Value, and Price Value on the Decision to Use NICE Bus Transportation - Intan Ramadhani; Emelia Rahmadany Putri Gami; Julianto Hutasuhut; Melisa Zuriani Hasibuan (Universitas Muhammadiyah Palu, 2025)
This study aims to analyze the influence of emotional value, social value, and price value on the decision to use NICE Bus transportation on the Kualanamu Airport – Millenium Plaza (Helvetia) route. Safe, comfortable, and affordable public transportation is an essential need for the community to support daily activities. However, the utilization of the NICE Bus is still not optimal due to varying perceptions regarding the emotional, social, and price aspects offered. This study uses a quantitative approach with a survey method by distributing questionnaires to 90 respondents who are NICE Bus users. The independent variables in this study are emotional value, social value, and price value, while the dependent variable is the usage decision. The data analysis technique uses multiple linear regression to test the simultaneous and partial influence of the three independent variables on the usage decision. The results of the study show that emotional value has a significant influence on the usage decision, particularly in terms of comfort and emotional satisfaction when using the NICE Bus. Social value also has a significant influence, especially regarding ease of access and travel efficiency perceived by passengers. Price value is proven to have a significant influence, indicating that affordable ticket prices that match the provided facilities are an important consideration in the usage decision. This study provides practical contributions for NICE Bus management in developing customer satisfaction-oriented marketing strategies to increase passenger volume and ensure the sustainability of transportation services.